Public reason, compromise within consensus, and legitimacy - Lim, Chong-Ming (De Gruyter, 2020)
A central idea of public reason liberalism is that the exercise of political power is legitimate when supported only by reasons which all citizens accept. Public reason serves as a necessary standard for evaluating the legitimacy of political decisions. In this paper, I examine the directive to employ public reason, from citizens’ perspective. I suggest that employing public reason potentially involves them engaging in different types of compromise. I consider how acknowledging these compromises sheds light on public reason liberalism. Public reason may not offer a necessary standard for evaluating the legitimacy of decisions, and the evaluation it offers may not have great weight relative to other moral and political considerations.